Internalization of Learning Motivation in Literary Text-Based Qiraah Learning - Muhammad Ridha; Muassomah (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
Learning motivation has become a serious problem in various educational institutions because it has implications for students’ interest and focuses on learning, the higher the motivation to learn, the higher the interest and focus of student learning. This research aims to instill students’ learning motivation through learning maharah qiraah (reading skills) using the teaching material of the story of Al-Hub Al-Maktum written by Prof. Drs. Muhaiban. This research uses a descriptive qualitative method to examine the data through data analysis of observations, interviews, and document studies with research samples from MA Al-Irsyad Tengaran 7 students in Batu City. The data field shows that students are less motivated by the learning materials that have been applied, which was implicated in the decreased interest and focus of students learning during teaching and learning activities. The results of the research show that there is an increase in students learning motivation in teaching and learning activities maharah qiraah using the teaching material of the story of Al-Hub Al-Maktum. These can be seen from the enthusiasm of students for participating in learning and the value calculations of before and after learning are increased by 9.96. The learning motivation that increases in students has able to influence student’s interest and focus on learning during teaching and learning activities.